Dampak Revitalisasi Pasar Tradisional terhadap Keberdayaan Pedagang di Pasar Desa Adat Intaran Sanur - Sudana, Ari; Ayuningsasi, A.A. Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 2, Februari 2016 (pp. 115 - 285), 2017)
This study aims to determine the perception of traders about the market performance after the revitalization of traditional markets in the Market Village People Intaran Sanur. This research was conducted at the Village Market Indigenous Intaran Sanur by using 72 samples as respondents. Data collected through interviews, observation, and questionnaires. Data analysis technique used is descriptive statistics to determine the perception of traders about the market performance after the revitalization of traditional markets in the Market Village People Intaran Sanur and factor analysis, and regression analysis to determine the effect of market performance against the empowerment of traders in the Market Village People Intaran Sanur. Based on factor analysis, known indicator that has the ability to explain the most high-performance variable to construct the market: guidance to the merchant. Based on the statistical t-test results, it can be concluded that the market performance positive and significant impact on the empowerment of the merchants in the Market Village People Intaran Sanur.
Keywords: Revitalisasi Pasar Tradisional, Persepsi Pedagang, Kinerja Pasar, Keberdayaan Pedagang